Design of the distributed control systems of hydrolithosphere processes - G. E. Veselov; M. I. Pershin (Известия высших учебных заведений: Геология и разведка)
The important problem of designing of control systems for the hydrolithosphere processes is considered. Many hydrolithosphere processes are known to be described by partial differential equations (belonging to the class of distributed objects), which mathematical models do not have analytical solutions. To assess the dynamic characteristics of the objects under consideration the approximation models are usually used. The method for determining the parameters of the approximation model is shown on the example of Arkhyz groundwater deposit. Main stages of the design of the systems under consideration are shown: the choice of the number of development wells; the construction of approximation models; adaptation of methods of synthesis of distributed control systems for the case of using the non-standard approximation models; the solution of the problem of synthesis of distributed control system of hydrolithosphere processes for a given deposit; the discrete form of the algorithm controlling the process; simulation of the closed-loop control system for the hydrolithosphere processes.